Factors Affecting Stock Prices through the Level of Capital Adequacy in Conventional Commercial Banks Listed on the Indonesia Stock Exchange in 2011-2020 - Daniel Surya Parapat; Erlina; Tarmizi (PT Mattawang Mediatama Solution, 2022)
This study aims to examine whether there is an effect of Loan to Deposit ratio (LDR), Non Performing Loan (NPL), Return on Assets (ROA), Net Interest Margin (NIM), Operating Expenses on Operating Income (BOPO) and Good Corporate Governance ( GCG) either directly or indirectly through the Capital Adequacy Level (CAR) on the Price of Stock. The population of this study is all conventional commercial bank companies listed on the Indonesia Stock Exchange in 2011-2020. The sampling method of this research used purposive sampling method and obtained 29 companies. The data used is secondary data in the form of company financial statements downloaded from www.idx.co.id. The data analysis technique used is path analysis with the help of the STATA statistical tool version 16. The results of this study indicate that LDR, NPL, ROA, NIM, BOPO, GCG simultaneously or jointly affect CAR by 12.94%, the remaining 87.06% is influenced by other factors. LDR, NPL, ROA, NIM, BOPO, GCG, CAR simultaneously or jointly affect the Price of Stock by 9.71%, the remaining 90.29% is influenced by other factors.